TOWARDS AN ISOTOPIC MODELING OF THE ILLITIZATION PROCESS BASED ON DATA OF ILLITE-TYPE FUNDAMENTAL PARTICLES FROM MIXED-LAYER ILLITE-SMECTITE - Clauer N. (My University, 2006)
Burial-induced and hydrothermal-related illitization in bentonites and in sandstones can be modeled on the basis of isotopic studies of fundamental particles separated from mixed-layer illite-smectite. The model envisages different reaction rates and durations relative to the varied impacts of temperature, considering that the water:rock ratio also has an influence. The different pathways for illitization are suggested on the basis of the K-Ar, Rb-Sr and δ18O compositions of previously studied materials. New information is provided on why fundamental particles separated from mixed-layer illite-smectite in shales yield K-Ar age data that are systematically greater than the ages of the fundamental particles from associated bentonites and/or sandstones, and greater than the reported stratigraphic ages. The study of pure authigenic, recent to present-day smectite from Pacific sediments shows that (1) those collected from active hydrothermal vents have 40Ar/36Ar ratios identical to that of the atmosphere, and (2) those of mud sediments have 40Ar/36 Ar ratios above the atmospheric value, indicating addition of 40Ar not generated in situ by radioactive decay. A preliminary but detailed analysis of the noble-gas (Ar, Xe, Kr) contents of authigenic smectite-rich size fractions from Pacific deep-sea red clays suggests trapping of these these gases by smectite. Therefore, the results point to the fact that fundamental particles can incorporate excess 40Ar into their structure when nucleating in restricted to closed systems, such as shales. This excess 40Ar, which represents radiogenie 40Ar released from nearby altered silicates, might be temporarily adsorbed at the surface of the rock pore spaces and is therefore available for incorporation in nucleating and growing particles. Copyright © 2006, The Clay Minerals Society.
Keywords: δ18O; BURIAL DIAGENESIS; CRYSTAL GROWTH; FUNDAMENTAL PARTICLES; HYDROTHERMAL ACTIVITY ILLITIZATION; K-AR; MIXED-LAYER ILLITE-SMECTITE; NOBLE GASES; NUCLEATION; RB-SR